بعض إسهامات العُمانيين في الحضارة الإسلامية - يونس محسن (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
كان للعمانيين إسهامات مهمة في مضمار الحضارة العربية الإسلامية, وقد تمثل ذلك في عدة مظاهر, أهمها الحركة الثقافية والفكرية, (من علوم دينية وفقهية ودراسات لغوية وأدبية) إلى جانب اهتماماتهم بالعلوم التاريخية والفلكية والملاحة البحرية. ويعد العمانيون من أوائل الشعوب الذين عرفوا التأليف الموسوعي. ونظراً لموقع عمان الجغرافي الهام المطل على مساحات هائلة من البحار والمحيطات, فقد وصفتهم المصادر العربية والفارسية والهندية والصينية والأوروبية بأنهم كانوا أمراء البحر وسادته وقد نشط أسطولهم في مجال التجارة والحرب ووصلت مراكبهم الهند والصين وجنوب شرق آسيا وبلاد الفرس وما بين النهرين وصولاً إلى مصر – عبر البحر الأحمر- وشرق آسيا, وقد ترتب على هذا الاتصال الواسع بالعامل الخارجي نتائج حضارية مهمة في الحياة الاقتصادية والاجتماعية والدينية التي سنتعرض لها من خلال محاور البحث بشيء من التفصيل والدقة. Omani people had important contributions in the field of Arab Islamic civilization. These contributions appeared in the intellectual and culture field (theology, linguistics, literature) besides being interested in history, astronomy and navigation. The Omanis showed interest in writing especially in the fields of religion and theology between the first and fifth Hijra centuries. Consequently, they established their own institutes. Moreover, Omanis were pioneers in encyclopedic literature. Due to Oman’s important position overlooking wide areas of seas and oceans, Omanis were described by the Indians, Chinese and Europeans as masters of the sea; their commercial and war navy reached India, china, south–east Asia, Persia, Mesopotamia, and Egypt via the red sea and eastern Africa. This contact produced important cultural results in all walks of life of which we will speak in more details.